PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 7E UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMAN 6 PEKANBARU - La Ada, Ariska Fifiyani Sangadji; ', Rini; Azmi, Johni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research about implementation of learning model Learning Cycle 7E has been done with purpose to improve learning result of students on the colloid subject at the class XI IPA SMAN 6 Pekanbaru. Learning model Learning Cycle 7E is cycle model that involve student actively through the 7 phase in learning process that is elicit, engage, explore, explain, elaborate, evaluate and extend. This research plan is experiment research by using Design Randomized Control Group pretest-posttest. The sample consist of two class that homogeneous, that is class XI IPA 4 as experiment class and class XI IPA 6 as control class. Experiment class constitute class that given implementation of learning model Learning Cycle 7E treatment, whereas control class that not given. The technic of data analyze used is t-test. Tabulation of data result obtained arithmetic-t bigger than table-t that is 3,43 bigger than 1,67, that can concluded that implementation learning model Learning Cycle 7E can improve student learning result on the colloid subject at the class XI IPA SMAN 6 Pekanbaru.Key Words: Learning Model Learning Cycle 7E, Learning Result, Colloid.